Acceptability and perceived utility of different diagnostic tests and sample types for trachoma surveillance in the Bijagos Islands, Guinea Bissau. (14th January 2021) - Sahota, Ramandeep Singh; Sanha, Salimato; Last, Anna; Cassama, Eunice; Goncalves, Adriana; Kelly, Ann H; Street, Alice; Harding-Esch, Emma M
Abstract: Background: Trachoma is the leading infectious cause of blindness worldwide and is nearing elimination as a public health problem in Guinea Bissau. It is imperative that elimination is followed by a successful postvalidation surveillance programme. The aim of this study was to determine the acceptability and perceived utility of different diagnostic tests and sample types that could be used for postvalidation trachoma surveillance in the Bijagos Islands, Guinea Bissau. Methods: Semistructured interviews with community members and stakeholders involved in trachoma elimination were followed by focus group discussions with community members, covering experiences with trachoma and views on trachoma diagnostic methods and sample types. Results: In this setting, all diagnostic tests and sample types used for trachoma surveillance were generally considered acceptable by communities. A preference for laboratory-based testing and finger-prick blood samples was expressed as these results were considered more accurate and applicable to a range of diseases beyond trachoma. Conclusions: Appropriate community and stakeholder engagement and communication regarding the purpose and processes around diagnostic practice prior to trachoma programme implementation are crucial for long-term successful disease-elimination efforts.